Keynes on Expectations, Uncertainty and Defensive Behavior - Carvalho, Fernando J. Cardim de (Brazilian Keynesian Review, 2015)
Keynesianism dominated macroeconomics until the early 1970s in the form of what was called hydraulic Keynesianism, a fundamentally mechanistic approach that assumed that economic agents always reacted in the same way to a certain set of stimuli. The dominance of hydraulic Keynesianism opened the way for the emerging criticism, first by Milton Friedman, and later by New Classical economists, that Keynesianism had no place for expectations. Keynes, however, dedicated close attention to the ways expectations were formed under fundamental uncertainty and how economic behavior was changed when agents acknowledged that the future was uncertain. For Keynes, acknowledging uncertainty meant that agents sought to take precautions against the possibility that their expectations were wrong and the decisions relying on them were incorrect. In The General Theory, Keynes showed that, in practically all fields, behavior would be significantly changed when agents acknowledged uncertainty. Precautionary savings, liquidity preference, conventional behavior, were all particular manifestations of the attempt to get protection against the losses that could result from the disappointment of expectations.